2019
DOI: 10.32776/revbiomed.v30i2.650
|View full text |Cite
|
Sign up to set email alerts
|

Rickettsia spp. en garrapatas (Acari: Ixodidae) que infestan perros de una comunidad rural con antecedentes de rickettsiosis, Yucatán, México

Abstract: Introducción. Las bacterias del género Rickettsia son agentes causales de las rickettsiosis, enfermedades zoonóticas endémicas en México. En Yucatán, ocurrió un brote en habitantes de Bolmay; sin embargo, no se identificó el probable artrópodo transmisor. Objetivo. Reportar la presencia de Rickettsia spp. en garrapatas infestando perros domésticos de Bolmay.Material y métodos. Se trabajaron 105 viales con hasta ocho garrapatas. Se extrajo ADN de los ectoparásitos, posterior a la identificación del ciclo de des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The infestation interval ranged between 1 and 8 specimens. Tick species found in the present study have been previously identified in Yucatan, Mexico ( Solís Hernández et al ., 2015 ; Rodríguez-Vivas et al ., 2016 ; Martínez-Ortiz et al ., 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…The infestation interval ranged between 1 and 8 specimens. Tick species found in the present study have been previously identified in Yucatan, Mexico ( Solís Hernández et al ., 2015 ; Rodríguez-Vivas et al ., 2016 ; Martínez-Ortiz et al ., 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Their importance is also reflected in the epidemiological fact that some active cases of rickettsiosis in humans have been associated with Rickettsia infection in these companion animals due to the closeness and coexistence with them, favouring the possibility of their ectoparasites passing to humans (Breitschwerdt et al, 1987). Likewise, domiciliated dogs are hosts of different genera of vector ticks (Martínez‐Ortiz et al, 2019) that can eventually parasitize humans and generate the zoonotic transmission cycle of Rickettsia (Saraiva et al, 2014; Torres‐Castro, Reyes‐Novelo, et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Although there are reports of rickettsial infections in native ticks (including species of Amblyomma, Haemaphysalis, Ixodes, and Ornithodoros) [21,41,42], to date, there is no confirmation of these ticks being vectors of TBPs or cause of clinical cases in dogs from CAC, despite the reports of E. canis in Amblyomma ovale in Yucatán and Rickettsia sp. in Ixodes affinis [21,43]. In the case of the causative agent of Q fever, Coxiella burnetii (formerly Rickettsia burnetii), little is known about its epidemiology and distribution within the CAC.…”
Section: Ticks and Tick-borne Bacterial And Protozoal Diseases In Animals In The Cacmentioning
confidence: 99%